2023
DOI: 10.1007/s11606-023-08117-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Unmet Social Needs and Care Access in a Veteran Cohort

Abstract: Background The association between unmet social needs (e.g., food insecurity) and adverse health outcomes is well-established, especially for patients with and at risk for cardiovascular disease (CVD). This has motivated healthcare systems to focus on unmet social needs. Yet, little is known about the mechanisms by which unmet social needs impact health, which limits healthcare-based intervention design and evaluation. One conceptual framework posits that unmet social needs may impact health by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Patients experiencing missingness may be positioned in precarious socioeconomic circumstances that expose them to disruptive forces that threaten health, material and social wellbeing [ 9 , 11 , 17 19 , 43 , 49 , 59 , 62 , 65 , 71 , 96 , 103 ]. Ideas of competing demands or “conflicting candidacies”([ 79 ], p.56) shows how multiple urgent and competing priorities might result in reduced prioritisation of health or appointment attendance relative to other needs [ 30 , 32 , 36 , 40 , 50 , 55 , 57 , 59 , 62 , 82 , 83 , 99 , 102 , 103 , 107 , 121 128 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients experiencing missingness may be positioned in precarious socioeconomic circumstances that expose them to disruptive forces that threaten health, material and social wellbeing [ 9 , 11 , 17 19 , 43 , 49 , 59 , 62 , 65 , 71 , 96 , 103 ]. Ideas of competing demands or “conflicting candidacies”([ 79 ], p.56) shows how multiple urgent and competing priorities might result in reduced prioritisation of health or appointment attendance relative to other needs [ 30 , 32 , 36 , 40 , 50 , 55 , 57 , 59 , 62 , 82 , 83 , 99 , 102 , 103 , 107 , 121 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…These demands include treatment burden and other appointments [ 4 , 10 , 11 , 15 , 17 , 19 , 28 , 41 , 43 , 44 , 48 , 59 , 61 , 62 , 64 , 73 , 83 , 84 , 86 , 93 , 100 , 128 – 135 ]; employment responsibilities, employer inflexibility and the financial costs of missing work [ 11 , 40 , 44 , 46 49 , 59 , 64 , 81 , 106 , 107 , 109 , 115 , 123 , 135 – 137 ]; and caring responsibilities taking precedence [ 14 , 40 , 41 , 44 , 48 , 59 , 64 , 99 , 131 , 138 ]. Patients experiencing severe and multiple disadvantages may have to prioritise accommodation, physical safety and survival demands over healthcare [ 43 , 48 , 53 , 64 , 65 , 69 , 71 , 81 , 96 , 103 , 114 , 139 ]. Travelling to appointments requires resources that may be limited or needed to meet other demands [ 27 , 28 , 30 –…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies assessing the use of mobile tools (eg, tablets) and telephone-based screening identified barriers to these screening modalities [ 12 - 14 ]. Barriers to using these methods include that tablets are dependent on patients presenting in person to the clinic [ 12 , 15 , 16 ] and phone-based screening may add additional work for already busy clinical staff [ 14 ].…”
Section: Introductionmentioning
confidence: 99%